Digital Leadership: Accelerating the Process of Talent Mobility and Job Rotation Efficiency in the Government Sector - Anggraini, Afriska Yuni; Sobandi, A.; Senen, Syamsul Hadi; Ahman, Eeng; Rofaida, Rofi (Dinasti Publisher, 2025)
This study explores the influence of digital leadership on job rotation and talent mobility within the public sector, addressing challenges posed by hierarchical structures and bureaucratic inertia. The research aims to determine whether digital leadership enhances these processes and fosters workforce adaptability. A quantitative approach utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to analyze data from 32 Ministry of Communication and Digital Affairs respondents. The findings reveal that digital leadership significantly impacts job rotation and talent mobility, with respective T-scores of 3.438 and 9.702 and P-values below the 0.05 threshold. Digital leadership explains 27.6% of the variance in job rotation and 61.7% in talent mobility, underscoring its role in streamlining career planning and cross-functional development. Tools such as predictive analytics and immersive technologies were identified as pivotal in enhancing talent management practices. This research highlights the transformative potential of digital leadership in overcoming public sector barriers, contributing to more responsive and agile organizational operations. By linking leadership strategies to workforce adaptability, this study provides actionable insights for improving public service efficiency and enriching the theoretical framework of digital leadership. These findings underscore the importance of fostering innovation and continuous learning in addressing contemporary organizational challenges.